Telur-telur penyuku / K.B. Ono ; editor Agus HK Soetomo ; ilustrasi Koespriyadi dan Budi Riyanto Karung - ONO KB; Agus HK Soetomo; Budi Riyadi Karung; Koespriyadi (Dian Rakyat, 2001)
36 hlm. : ilus. ; 23 cm + CD